2021
DOI: 10.1186/s43141-021-00205-3
|View full text |Cite
|
Sign up to set email alerts
|

Clonal hematopoiesis of indeterminate potential (CHIP) and cardiovascular diseases—an updated systematic review

Abstract: Background Cardiovascular diseases (CVDs) are the leading cause of mortality in India. Residual risk exists in patients receiving optimal guideline-directed medical therapy. Possession of certain somatic mutations, at a variant allele frequency of ≥ 2% in peripheral blood, driving clonal expansion in the absence of cytopenias and dysplastic hematopoiesis is defined as clonal hematopoiesis of indeterminate potential (CHIP). Recently, it was found that carriers of CHIP had a higher risk to have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…7,8 CH has been associated with numerous adverse health outcomes, including an increased incidence of hematological malignancies, 3,4,9 adverse cancer outcomes, 10,11 risk of infections, 12,13 osteoporosis, 14 and cardiovascular disease. [15][16][17] Together, these associations appear to largely explain the inferior survival that is seen in individuals with CH. 3,4 The relationship between CH and subsequent hematological malignancies is complex with tumor cell autonomous and non-cell autonomous effects.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…7,8 CH has been associated with numerous adverse health outcomes, including an increased incidence of hematological malignancies, 3,4,9 adverse cancer outcomes, 10,11 risk of infections, 12,13 osteoporosis, 14 and cardiovascular disease. [15][16][17] Together, these associations appear to largely explain the inferior survival that is seen in individuals with CH. 3,4 The relationship between CH and subsequent hematological malignancies is complex with tumor cell autonomous and non-cell autonomous effects.…”
Section: Introductionmentioning
confidence: 93%
“…The concept of CH has been extended to mosaic chromosomal alterations that, similar to mutation‐defined CH, increases in frequency with advancing age 7,8 . CH has been associated with numerous adverse health outcomes, including an increased incidence of hematological malignancies, 3,4,9 adverse cancer outcomes, 10,11 risk of infections, 12,13 osteoporosis, 14 and cardiovascular disease 15–17 . Together, these associations appear to largely explain the inferior survival that is seen in individuals with CH 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Clonal hematopoiesis of indeterminate potential (CHIP), a collection of somatic mutations, is an age-associated risk factor for MI, stroke, heart failure events, and survival following percutaneous aortic valve intervention ( 129 , 130 ). It is suggested that CHIP activates the inflammasome pathway and contributes to thrombosis, leading to CVD.…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…Inflammatory macrophages are instrumental to the pathogenesis of atherosclerosis. Therefore, the resulting positive feedback loop between CHIP and chronic inflammation increases the risk of development of atherosclerosis and chronic heart failure [ 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%